Racial Harassment, Job Satisfaction and Intentions to Quit: Evidence from the British Nursing Profession - Michael A. Shields (Institute for the Study of Labor (IZA), 2000)
This paper investigates the determinants of racial harassment at the workplace and its impact, via job satisfaction, on intentions to quit. Using data for ethnic minority nurses in Britain, we find that nearly 40% of nurses have experienced racial harassment from work colleagues, whilst more than 64% have suffered racial harassment from patients. The experience of racial harassment at the workplace leads to a significant reduction in job satisfaction, which, in turn, significantly increases nurses? intentions to quit their job. These findings have important policy implications for retaining qualified nursing staff in the British National Health Service.
Keywords: J24; J71; J15; 330; Racial harassment; nursing; job satisfaction; intentions to quit; Ethnische Diskriminierung; Arbeitszufriedenheit; Arbeitsmobilität; Pflegeberufe; Schätzung; Großbritannien